Exploring Pharmacy Frontliners Experience in Using the Mosly Application: A Qualitative Study of Reward and Digital Service Quality - Harits Farsyah; Anita Safitri (STIE Amkop Makassar, 2026)
Digital transformation in the pharmaceutical sector has encouraged the adoption of digital loyalty programs to strengthen user engagement and support sales activities. The Mosly application is one such program, developed for pharmacy frontliners to record product sell out, monitor points, and redeem rewards. This study aims to explore pharmacy frontliners’ experience in using the Mosly application in terms of ease of use, reward feature accessibility, and digital service quality. A descriptive qualitative approach was applied through structured direct observation of 20 frontliners from 20 active user pharmacies across three core activities: login, sell out input, and reward redemption. Data were analyzed using the interactive model of Miles, Huberman, and Saldana. The results show that login succeeded in 18 of 20 pharmacies, sell out input was performed independently by 10 pharmacies while 9 required assistance, whereas reward redemption was independent in only 8 pharmacies, with 8 requiring assistance, 1 failing due to an error, and 3 untested. Based on five e-service quality dimensions, service quality was adequate, with responsiveness as the strongest and error handling as the weakest dimension. Technical issues concentrated on low-specification devices and older Android versions, indicating that device compatibility critically shapes digital service quality. The study contributes by applying e-service quality dimensions as a behavior-based analytical framework and offers practical implications for improving the application and its loyalty program.